Pengaruh Motivasi Terhadap Kinerja Pegawai Sekretariat Daerah Provinsi Maluku - Prisilya Patty; Jean Rosalina Asthenu; Vera Paulin Kay; Vascolino Pattipeilohy (Jurnal Administrasi Terapan, 2026)
A preliminary survey at the General Bureau of the Maluku Provincial Secretariat indicated motivational issues affecting employee performance. This study aims to determine how motivation affects employee performance at the General Bureau of the Maluku Provincial Secretariat.The analytical methods used in this study were quantitative analysis and simple linear regression. Descriptive analysis showed that motivation at the General Bureau of the Maluku Provincial Secretariat had an average score of 3.55, which is interpreted as good, while employee performance had an average score of 3.59, which is interpreted as good. The regression analysis results indicate that motivation has a positive effect on employee performance at the General Bureau of the Maluku Provincial Secretariat.Based on these results, it can be concluded that poor motivation will lead to decreased employee performance. To address this, the General Bureau of the Maluku Provincial Secretariat can strive to ensure that leaders are able to provide adequate supervision and technical skills appropriate to their positions, as well as to enable employees to work independently without supervision and continually strive to develop their skills while working.Keywords: Motivation, Performance